Preparation method and application of MXene-based sodium ion battery negative electrode material
By preparing the MXene/SnS2/SnO2 composite material, the poor circulation performance and structural stability of metal compound materials at the negative end of sodium ion battery are solved, and high specific capacity and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202411856731.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
Metal compound materials have poor circulation performance at the negative end of sodium ion batteries, and there are problems such as large volume expansion and poor structural stability during charging and discharging.
Using the preparation method of MXene/SnS2/SnO2 composite material, the alkali metal fluoride is mixed with an acid solution, and the MAX phase material is added to react, and the MXene suspension is obtained by ultrasonic reaction; the tin source and sulfur source are reacted in an autoclave, and the SnS2/SnO2 mixture is obtained, and the two are mixed and ultrasonic are prepared to obtain the MXene/SnS2/SnO2 composite material.
It improves the specific capacity and cycle stability of sodium ion batteries and has excellent rate performance, solving the problem of insufficient performance of metal compound materials at the negative end of sodium ion batteries.
Smart Images

Figure CN119764377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and specifically relates to a preparation method and application of a MXene-based sodium ion battery negative electrode material. Background Art
[0002] In recent years, with the further growth of people's demand for power batteries, sodium-ion batteries (SIBs) with similar principles to lithium-ion batteries have attracted much attention. Compared with metallic lithium, metallic sodium has the advantages of high resource reserves and low cost, but the sodium-ion batteries composed of it have low energy density and poor cycle performance. One of the reasons is that the current mainstream sodium-ion battery hard carbon negative electrode material has a low specific capacity. Therefore, finding a negative electrode material that can take into account both high specific capacity and cycle performance is one of the breakthroughs to accelerate the commercialization of sodium-ion batteries. The negative electrode materials of sodium-ion batteries are mainly divided into five categories: carbon-based materials, titanium-based compounds, alloy materials, metal compounds and organic compounds. Among them, the research and development technology of carbon-based materials is mature, and hard carbon (HC) is the current mainstream negative electrode material, but its specific capacity and rate performance need to be improved. Metal compound materials are based on their high conductivity, high specific energy and excellent rate performance, but their cycle performance is poor, and there are problems such as large volume expansion and poor structural stability during charging and discharging, which further limits the application of metal compounds in the negative end of sodium-ion batteries.
[0003] At present, in response to the many problems existing in metal compounds, there are related reports on nanostructure design and carbon coating of metal compounds to improve the electrochemical properties of metal compounds. For example, invention CN114425370A uses CuCo2S4, sodium molybdate and thiourea as raw materials to prepare MoS2@CuCo2S4 composite materials through hydrothermal reaction. Patent CN112366319A uses microwave-assisted sol-gel method to prepare nano SnO2 while introducing mesophase carbon microsphere material, and then undergoes a series of high-temperature treatments to obtain nano tin oxide-mesophase carbon microsphere composite materials. However, the materials obtained by the above inventions cannot take into account both high specific energy and high rate performance. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a MXene-based sodium ion battery negative electrode material to solve the problems of poor cycle performance of metal compound materials, large volume expansion during charge and discharge, and poor structural stability.
[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions: The present invention discloses a method for preparing a MXene / SnS2 / SnO2 composite material, comprising: S1: Alkali metal fluoride is mixed with an acid solution, and MAX phase material is added to react, and then a precipitate is obtained by washing and separation. The precipitate is added to water and ultrasonicated to obtain a MXene suspension; S2: Add a tin source and a sulfur source into water and mix them, transfer them to an autoclave for reaction, then wash and separate the precipitate, add the precipitate into water and ultrasonically obtain a SnS2 / SnO2 mixed solution; the sulfur source includes at least one of thioacetamide, thiourea, dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid, and the dithiocarbamate is obtained by the reaction of bis(2-cyanoethyl)amine and carbon disulfide; the use of dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid not only provides an efficient sulfur source, but also can affect the morphology of SnS2 / SnO2 and the specific surface area of the material, which is beneficial to the transfer and diffusion of sodium ions, thereby improving the electrochemical performance of batteries made of MXene / SnS2 / SnO2 composite materials.
[0006] S3: The MXene suspension and the SnS2 / SnO2 mixed solution are mixed by ultrasound, and then filtered, washed and dried to obtain a MXene / SnS2 / SnO2 composite material.
[0007] Preferably, the alkali metal fluoride in S1 is lithium fluoride.
[0008] Preferably, the acid solution in S1 is a hydrochloric acid solution, which consists of hydrochloric acid and water, the usage ratio of hydrochloric acid to water is 1 mol: 0.08-0.17 L, and the mass ratio of the usage of alkali metal fluoride to the usage of hydrochloric acid solution is 1: 5-10.
[0009] Preferably, the MAX phase material in S1 is titanium aluminum carbide, and the mass ratio of the amount of alkali metal fluoride used to the amount of MAX phase material used is 1:0.8-2.
[0010] Preferably, the tin source in S2 includes at least one of tin chloride pentahydrate and stannous chloride, the mass ratio of the tin source to the sulfur source is 1:1-4, and the amount of the tin source added to the water is 0.002-0.01 g / ml.
[0011] Preferably, the amount of MXene suspension precipitate in S1 is measured as alkali metal fluoride, and the mass ratio of the amount of alkali metal fluoride used to the amount of tin source used in S2 is 1:1.5-4.5.
[0012] Preferably, after adding the MAX phase material to S1, the reaction temperature is 25-35°C, the reaction time is 13-20h, and the ultrasonic time is 0.8-1.5h.
[0013] Preferably, in S2, the reaction temperature in the autoclave is 150-180° C., the reaction time is 12-20 h, and the ultrasonic time is 0.8-1.5 h.
[0014] Preferably, the ultrasonic time in S3 is 4-8 hours.
[0015] The present invention discloses a battery, comprising a MXene / SnS2 / SnO2 composite material prepared by any of the above methods.
[0016] The present invention discloses a method for preparing a MXene / SnS2 / SnO2 composite material, specifically: Alkali metal fluoride is mixed with acid solution, MAX phase material is added and reacted at 25-35℃ for 13-20h, a precipitate is obtained after washing and separation, and the precipitate is added to water and ultrasonicated for 0.8-1.5h to obtain a MXene suspension. Tin source and sulfur source are added to water and mixed, transferred to an autoclave and reacted at 150-180℃ for 12-20h, and then washed and separated to obtain a precipitate, and the precipitate is added to water and ultrasonicated for 0.8-1.5h to obtain a SnS2 / SnO2 mixed solution. The MXene suspension and the SnS2 / SnO2 mixed solution are mixed and ultrasonicated for 4-8h, and then filtered, washed and dried to obtain a MXene / SnS2 / SnO2 composite material.
[0017] Preferably, the alkali metal fluoride is lithium fluoride.
[0018] Preferably, the acid solution is a hydrochloric acid solution, which consists of hydrochloric acid and water, the usage ratio of hydrochloric acid to water is 1 mol: 0.08-0.17 L, and the mass ratio of the usage of alkali metal fluoride to the usage of hydrochloric acid solution is 1: 5-10.
[0019] Preferably, the MAX phase material is titanium aluminum carbide, and the mass ratio of the amount of alkali metal fluoride used to the amount of MAX phase material used is 1:0.8-2.
[0020] Preferably, the tin source includes at least one of tin chloride pentahydrate and stannous chloride.
[0021] Preferably, the sulfur source includes at least one of thioacetamide, thiourea, dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid.
[0022] Preferably, the mass ratio of the amount of the tin source used to the amount of the sulfur source used is 1:1-4, and the amount of the tin source added to the water is 0.003-0.01 g / ml.
[0023] Preferably, the amount of MXene suspension precipitate is measured in terms of alkali metal fluoride, and the mass ratio of the amount of alkali metal fluoride used to the amount of tin source used in S2 is 1:1.5-4.5.
[0024] Preferably, when preparing MXene suspension and SnS2 / SnO2 mixed solution, the washing reagent is water, and when preparing MXene / SnS2 / SnO2 composite material, the washing reagent is anhydrous ethanol.
[0025] The present invention discloses a method for preparing dithiocarbamate, which is specifically: Add bis(2-cyanoethyl)amine to acetonitrile, lower the temperature to -2-5°C, then drop carbon disulfide and sodium hydroxide solution into the mixture and react for 20-50 minutes. Allow to stand and filter, and dry the filtrate at 40-50°C to obtain dithiocarbamate.
[0026] Preferably, the usage ratio of bis(2-cyanoethyl)amine to acetonitrile is 1 mol:20-30 ml.
[0027] Preferably, the molar ratio of the amount of carbon disulfide used to the amount of bis(2-cyanoethyl)amine used is 1:0.6-1.5.
[0028] Preferably, the ratio of the amount of sodium hydroxide solution to the amount of bis(2-cyanoethyl)amine is 1 mol:75-85 ml, the sodium hydroxide solution consists of sodium hydroxide and water, and the mass ratio of the amount of sodium hydroxide to water is 1:0.8-1.5.
[0029] More preferably, in the preparation of MXene / SnS2 / SnO2 composite materials, a copolymer surfactant can be used on the basis of using a sulfur source. The sulfur source is dithiocarbamate and 2-mercapto-S-thiobenzoyl acetic acid. Used together with the copolymer surfactant, the copolymer surfactant can assist tin chloride pentahydrate, dithiocarbamate and 2-mercapto-S-thiobenzoyl acetic acid to synthesize the SnS2 / SnO2 mixed solution, inhibit the agglomeration of the synthesized SnS2 / SnO2, form a uniform and smooth morphology, and thus improve the electrochemical performance of the battery made of the MXene / SnS2 / SnO2 composite material.
[0030] Preferably, the mass ratio of the amount of dithiocarbamate used to the amount of copolymer surfactant used is 1:0.2-0.75.
[0031] The present invention discloses a method for preparing a copolymer surfactant, comprising: Under nitrogen conditions, maleic acid, p-toluenesulfonic acid and hydroquinone are added to lauryl alcohol polyoxyethylene ether, and the reaction is carried out at 110-130° C. for 4-7 hours. After the reaction is completed, the intermediate is dried to obtain an intermediate, the pH of the intermediate is adjusted to 6-8, and then acrylic acid, 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, ammonium persulfate and water are added, and the reaction is carried out at 75-85° C. for 4-7 hours. The pH is then adjusted to 8-10, and then tetrahydrofuran is added to obtain a dissolving solution, and then methanol is added to precipitate, and the precipitate is dried to obtain a copolymer surfactant.
[0032] Preferably, the molar ratio of the amount of lauryl alcohol polyoxyethylene ether used to the amount of maleic acid used is 1:0.8-1.5.
[0033] Preferably, the mass ratio of maleic acid to p-toluenesulfonic acid is 1:0.05-0.1.
[0034] Preferably, the mass ratio of maleic acid to hydroquinone is 1:0.004-0.01.
[0035] Preferably, the reagent used to adjust the pH is a sodium hydroxide solution, which consists of sodium hydroxide and water, and the dosage ratio of sodium hydroxide to water is 1g:3-6ml.
[0036] Preferably, the molar ratio of the amount of the intermediate used to the amount of 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt used is 1:0.3-0.8.
[0037] Preferably, the molar ratio of the amount of acrylic acid used to the amount of 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt used is 1:0.3-0.8.
[0038] Preferably, the mass ratio of the amount of the intermediate used to the amount of ammonium persulfate used is 1:0.02-0.035.
[0039] Preferably, the usage ratio of the intermediate to water is 1 mol: 90-140 ml.
[0040] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a preparation method and application of a MXene-based sodium ion battery negative electrode material, wherein an MXene suspension is obtained by ultrasonically reacting an alkali metal fluoride, an acid solution and a MAX phase material; a SnS2 / SnO2 mixed solution is obtained by calcining a tin source and a sulfur source in an autoclave, and ultrasonically reacting the MXene suspension and the SnS2 / SnO2 mixed solution; and a MXene / SnS2 / SnO2 composite material is prepared by ultrasonically mixing the MXene suspension and the SnS2 / SnO2 mixed solution. The sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared by the present invention exhibits high specific capacity and excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0042] Figure 1 Schematic diagram of the MXene / SnS2 / SnO2 structure; Figure 2 This is a comparison chart of cycle performance test; Figure 3 This is a comparison chart of rate performance test. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0045] Embodiment 1: Preparation of MXene / SnS2 / SnO2 composite material: First, lithium fluoride is mixed with hydrochloric acid solution, and then titanium aluminum carbide is added, and the reaction is carried out at 25°C for 16 hours. After the reaction, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a MXene suspension. Then, tin chloride pentahydrate and thioacetamide are added to water to obtain a mixed solution, and the mixed solution is transferred to an autoclave, and reacted at 160°C for 15 hours. After the reaction, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a SnS2 / SnO2 mixed solution. Finally, the MXene suspension and the SnS2 / SnO2 mixed solution are mixed and ultrasonicated for 5 hours. After the ultrasonication, the precipitate is vacuum filtered to obtain the precipitate, washed with anhydrous ethanol, and then dried at 60°C for 6 hours to obtain a MXene / SnS2 / SnO2 composite material. The mass ratio of lithium fluoride to hydrochloric acid solution is 1:8, the hydrochloric acid solution is composed of hydrochloric acid and water, the mass ratio of hydrochloric acid to water is 1 mol: 0.11 L, the mass ratio of lithium fluoride to titanium aluminum carbide is 1:1, the mass ratio of tin chloride pentahydrate to thioacetamide is 1:1.5, the amount of tin chloride pentahydrate added to water is 0.005 g / ml, the amount of MXene suspension precipitate is measured in lithium fluoride, and the mass ratio of lithium fluoride to tin chloride pentahydrate is 1:4. The structure of MXene / SnS2 / SnO2 composite material is as follows: Figure 1 As shown, 2DSnS2 and 0D SnO2 are randomly interspersed between the MXene layers.
[0046] Embodiment 2: Preparation of dithiocarbamate: add bis(2-cyanoethyl)amine to acetonitrile, lower the temperature to 0°C, then drop carbon disulfide and sodium hydroxide solution, continue the reaction for 30 minutes, filter to obtain a filtrate, and dry the filtrate at 45°C to obtain dithiocarbamate. The ratio of bis(2-cyanoethyl)amine to acetonitrile is 1 mol:25 ml, the molar ratio of carbon disulfide to bis(2-cyanoethyl)amine is 1:1, the ratio of sodium hydroxide solution to bis(2-cyanoethyl)amine is 1 mol:80 ml, and the sodium hydroxide solution is composed of sodium hydroxide and water, and the mass ratio of sodium hydroxide to water is 1:1.
[0047] Preparation of MXene / SnS2 / SnO2 composite material: First, lithium fluoride is mixed with hydrochloric acid solution, and then titanium aluminum carbide is added, and the reaction is carried out at 25°C for 16 hours. After the reaction is completed, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a MXene suspension. Then, tin chloride pentahydrate, dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid are added to water to obtain a mixed solution, and the mixed solution is transferred to an autoclave, and reacted at 160°C for 15 hours. After the reaction is completed, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a SnS2 / SnO2 mixed solution. Finally, the MXene suspension and the SnS2 / SnO2 mixed solution are mixed and ultrasonicated for 5 hours. After the ultrasonication is completed, the precipitate is vacuum filtered to obtain the precipitate, washed with anhydrous ethanol, and then dried at 60°C for 6 hours to obtain a MXene / SnS2 / SnO2 composite material. The mass ratio of lithium fluoride to hydrochloric acid solution is 1:8, the hydrochloric acid solution is composed of hydrochloric acid and water, the mass ratio of hydrochloric acid to water is 1 mol: 0.11 L, the mass ratio of lithium fluoride to titanium aluminum carbide is 1:1, the mass ratio of tin chloride pentahydrate to dithiocarbamate is 1:0.8, the mass ratio of tin chloride pentahydrate to 2-mercapto-S-thiobenzoylacetic acid is 1:0.7, the amount of tin chloride pentahydrate added to water is 0.005 g / ml, the amount of MXene suspension precipitate is measured in lithium fluoride, and the mass ratio of lithium fluoride to tin chloride pentahydrate is 1:4.
[0048] Embodiment 3: The preparation of dithiocarbamate is the same as in Example 2.
[0049] Preparation of MXene / SnS2 / SnO2 composite materials: The preparation of MXene / SnS2 / SnO2 composite materials in this embodiment is compared with that in Example 2, except that the mass ratio of tin chloride pentahydrate used to dithiocarbamate used is 1:1.3, and other conditions and parameters are the same as in Example 2.
[0050] Embodiment 4: The preparation of dithiocarbamate is the same as in Example 2.
[0051] Preparation of MXene / SnS2 / SnO2 composite materials: The preparation of MXene / SnS2 / SnO2 composite materials in this embodiment is compared with that in Example 2, except that the mass ratio of tin chloride pentahydrate used to 2-mercapto-S-thiobenzoylacetic acid used is 1:1, and other conditions and parameters are the same as in Example 2.
[0052] Embodiment 5: The preparation of dithiocarbamate is the same as in Example 2.
[0053] Preparation of copolymer surfactant: maleic acid, p-toluenesulfonic acid and hydroquinone are added to lauryl alcohol polyoxyethylene ether under nitrogen conditions, and the reaction is carried out at 120°C for 5 hours. After the reaction is completed, the intermediate is dried to obtain an intermediate. Sodium hydroxide solution is added to the intermediate to adjust the pH to 7, and then acrylic acid, 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, ammonium persulfate and water are added, and the reaction is carried out at 80°C for 5 hours. After the reaction is completed, sodium hydroxide solution is added to adjust the pH to 9, and then tetrahydrofuran is added to obtain a dissolving solution, methanol is added to the dissolving solution to precipitate, and the precipitate is dried to obtain a copolymer surfactant. The molar ratio of lauryl alcohol polyoxyethylene ether to maleic acid is 1:1.1, the mass ratio of maleic acid to p-toluenesulfonic acid is 1:0.07, the mass ratio of maleic acid to hydroquinone is 1:0.006, the sodium hydroxide solution consists of sodium hydroxide and water, the amount ratio of sodium hydroxide to water is 1g:4ml, the molar ratio of the intermediate to 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt is 1:0.5, the molar ratio of acrylic acid to 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt is 1:0.5, the mass ratio of the intermediate to ammonium persulfate is 1:0.025, and the amount ratio of the intermediate to water is 1mol:100ml.
[0054] Preparation of MXene / SnS2 / SnO2 composite material: First, lithium fluoride is mixed with hydrochloric acid solution, and then titanium aluminum carbide is added, and the reaction is carried out at 25°C for 16 hours. After the reaction is completed, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a MXene suspension. Then, tin chloride pentahydrate, dithiocarbamate, 2-mercapto-S-thiobenzoyl acetic acid and copolymer surfactant are added to water to obtain a mixed solution, and the mixed solution is transferred to an autoclave, and reacted at 160°C for 15 hours. After the reaction is completed, it is washed with water, and the precipitate is separated. The precipitate is added to water and ultrasonicated for 1 hour to obtain a SnS2 / SnO2 mixed solution. Finally, the MXene suspension and the SnS2 / SnO2 mixed solution are mixed and ultrasonicated for 5 hours. After the ultrasonication is completed, the precipitate is vacuum filtered to obtain the precipitate, washed with anhydrous ethanol, and then dried at 60°C for 6 hours to obtain a MXene / SnS2 / SnO2 composite material. The mass ratio of lithium fluoride to hydrochloric acid solution is 1:8, the hydrochloric acid solution is composed of hydrochloric acid and water, the mass ratio of hydrochloric acid to water is 1 mol: 0.11 L, the mass ratio of lithium fluoride to titanium aluminum carbide is 1:1, the mass ratio of tin chloride pentahydrate to dithiocarbamate is 1:0.8, the mass ratio of tin chloride pentahydrate to 2-mercapto-S-thiobenzoylacetic acid is 1:0.7, the mass ratio of dithiocarbamate to copolymer surfactant is 1:0.34, the amount of tin chloride pentahydrate added to water is 0.005 g / ml, the amount of MXene suspension precipitate is measured in lithium fluoride, and the mass ratio of lithium fluoride to tin chloride pentahydrate is 1:4.
[0055] Embodiment 6: The preparation of dithiocarbamate is the same as in Example 2.
[0056] The preparation of the copolymer surfactant is the same as in Example 5.
[0057] Preparation of MXene / SnS2 / SnO2 composite materials: The preparation of MXene / SnS2 / SnO2 composite materials in this embodiment is compared with that in Example 5, except that the mass ratio of the amount of dithiocarbamate used to the amount of copolymer surfactant used is 1:0.6, and other conditions and parameters are the same as in Example 2.
[0058] Comparative Example 1: Preparation of MXene / SnS2 / SnO2 composite material: The preparation of MXene / SnS2 / SnO2 composite material in this embodiment is compared with Example 2, except that dithiocarbamate is not used, and other conditions and parameters are the same as Example 2.
[0059] Comparative Example 2: Preparation of MXene / SnS2 / SnO2 composite material: The preparation of MXene / SnS2 / SnO2 composite material in this embodiment is compared with Example 2, except that 2-mercapto-S-thiobenzoylacetic acid is not used, and other conditions and parameters are the same as Example 2.
[0060] Experimental Example 1: Preparation of sodium ion battery. Mix MXene / SnS2 / SnO2 composite material, acetylene black and PVDF solution, then drop N-methylpyrrolidone and stir for 6 hours. Then apply it on copper foil and vacuum dry it at 70°C for 5h. After drying, slice it to obtain the negative electrode sheet. In an argon glove box, assemble and seal the positive electrode shell, negative electrode sheet, glass fiber diaphragm, sodium sheet, NaClO4+EC / PC(1:1)v / v+5%FEC electrolyte, shrapnel, gasket and negative electrode shell to obtain a sodium ion battery. The mass ratio of MXene / SnS2 / SnO2 composite material to acetylene black is 1:0.21, the mass ratio of acetylene black to PVDF solution is 1:1, and the mass ratio of N-methylpyrrolidone to PVDF solution is 1:1.5. The MXene / SnS2 / SnO2 composite materials include the MXene / SnS2 / SnO2 composite materials prepared in Examples 1-6 and Comparative Examples 1-2.
[0061] The cycle performance was measured by charging and discharging the sodium ion battery made of MXene / SnS2 / SnO2 composite material at 25°C and 0.05A / g, with a voltage range of 0.01-2.5V. The cycle performance was compared after 300 cycles.
[0062] Table 1 Capacity retention rate measurement results
[0063] The results are shown in Table 1. The sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared in Example 1 of the present invention has a lower capacity retention rate than that of Example 2, indicating that the use of dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid can improve the capacity retention rate, i.e., the cycle performance, of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material. Compared with Example 2, Example 3 shows that the increase in the use of dithiocarbamate within a certain range can improve the capacity retention rate of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material. Compared with Example 2, Example 4 shows that the increase in the use of 2-mercapto-S-thiobenzoylacetic acid within a certain range can improve the capacity retention rate of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material. Example 5 Compared with Example 2, it is shown that on the basis of using dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid, the use of copolymer surfactants can further improve the capacity retention rate of sodium ion batteries made of MXene / SnS2 / SnO2 composite materials; Example 6 shows that increasing the use amount of copolymer surfactants within a certain range can improve the capacity retention rate of sodium ion batteries made of MXene / SnS2 / SnO2 composite materials; Comparative Examples 1 and 2, compared with Example 2, show that dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid need to be used together, and the use of any one of dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid alone has no obvious effect on improving the capacity retention rate of sodium ion batteries made of MXene / SnS2 / SnO2 composite materials.
[0064] Experimental Example 2: The preparation of the sodium ion battery is the same as that of Experimental Example 1. The MXene / SnS2 / SnO2 composite material includes the MXene / SnS2 / SnO2 composite material prepared in Examples 1-6 and Comparative Examples 1-2.
[0065] The initial specific capacity of the battery was measured at 25°C and 0.05A / g for the sodium ion battery made of MXene / SnS2 / SnO2 composite material, with a voltage range of 0.01-2.5V.
[0066] Table 2 Initial specific capacity measurement results
[0067] The results are shown in Table 2. The initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared in Example 1 of the present invention is lower than that in Example 2, indicating that the use of dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid can improve the initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material; Example 3, compared with Example 2, shows that the increase in the use of dithiocarbamate within a certain range can improve the initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material; Example 4, compared with Example 2, shows that the increase in the use of 2-mercapto-S-thiobenzoylacetic acid within a certain range can improve the initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material; Example 5, compared with Example 2, shows that the increase in the use of 2-mercapto-S-thiobenzoylacetic acid within a certain range can improve the initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material. Compared with Example 2, it is shown that the use of copolymer surfactants on the basis of dithiocarbamates and 2-mercapto-S-thiobenzoylacetic acid can further improve the initial specific capacity of the sodium ion battery made of MXene / SnS2 / SnO2 composite materials; Example 6 is compared with Example 5, indicating that the increase in the use of copolymer surfactants within a certain range can improve the initial specific capacity of the sodium ion battery made of MXene / SnS2 / SnO2 composite materials; Comparative Examples 1 and 2 are compared with Example 2, indicating that dithiocarbamates and 2-mercapto-S-thiobenzoylacetic acid need to be used together, and the use of any one of dithiocarbamates and 2-mercapto-S-thiobenzoylacetic acid alone has no obvious effect on the improvement of the initial specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material.
[0068] Experimental Example 3: The preparation of the sodium ion battery is the same as that of Experimental Example 1. The MXene / SnS2 / SnO2 composite material is the MXene / SnS2 / SnO2 composite material prepared in Example 1.
[0069] In the cycle performance test, the sodium ion battery made of MXene / SnS2 / SnO2 composite material and the traditional HC battery were charged and discharged at 25°C and 0.05A / g, with a voltage range of 0.01-2.5V, to compare the cycle performance of the two batteries.
[0070] The results are as follows Figure 2As shown, compared with the conventional HC battery, the sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared in Example 1 has a faster decay rate of the specific capacity of the conventional HC battery as the number of cycles increases. After 300 cycles, the specific capacity of the conventional HC battery is 237.1 mAh / g, and the capacity retention rate is 81.93%. The specific capacity of the sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared in Example 1 is 505.4 mAh / g, and the capacity retention rate is 94.09%, indicating that the sodium ion battery made of the MXene / SnS2 / SnO2 composite material prepared in Example 1 of the present invention has better specific capacity and cycle performance.
[0071] Experimental Example 4: The preparation of the sodium ion battery is the same as that of Experimental Example 1. The MXene / SnS2 / SnO2 composite material is the MXene / SnS2 / SnO2 composite material prepared in Example 1.
[0072] In the rate performance test, sodium-ion batteries made of MXene / SnS2 / SnO2 composite materials and traditional HC batteries were cyclically charged and discharged at different current densities (0.05A / g, 0.1A / g, 0.2A / g, 0.4A / g, 0.6A / g, 0.8A / g, and 1A / g). Each current density was cycled for 10 cycles, and finally returned to a current density of 50 mA / g for 10 cycles to end the test.
[0073] The results are as follows Figure 3 As shown in the figure, with the increase of current density, the specific capacity of the sodium ion battery made of MXene / SnS2 / SnO2 composite materials and the traditional HC battery gradually decreases. When the current density drops from 1A / g to 0.05A / g, the specific capacity of the sodium ion battery made of MXene / SnS2 / SnO2 composite materials rises from 382.1mAh / g to 527.8mAh / g, which has better rate performance than the traditional HC battery.
[0074] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0075] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for preparing a MXene / SnS2 / SnO2 composite material, comprising: S1: Alkali metal fluoride is mixed with an acid solution, and MAX phase material is added to react, and then a precipitate is obtained by washing and separation. The precipitate is added to water and ultrasonicated to obtain a MXene suspension; S2: adding a tin source and a sulfur source into water and mixing them, transferring them to an autoclave for reaction, then washing and separating a precipitate, adding the precipitate into water and ultrasonically obtaining a SnS2 / SnO2 mixed solution; the sulfur source comprises at least one of thioacetamide, thiourea, dithiocarbamate and 2-mercapto-S-thiobenzoylacetic acid, and the dithiocarbamate is obtained by reacting bis(2-cyanoethyl)amine and carbon disulfide; S3: The MXene suspension and the SnS2 / SnO2 mixed solution are mixed by ultrasound, and then filtered, washed and dried to obtain a MXene / SnS2 / SnO2 composite material.
2. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The alkali metal fluoride in S1 is lithium fluoride.
3. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The acid solution in S1 is a hydrochloric acid solution, which consists of hydrochloric acid and water, the usage ratio of hydrochloric acid to water is 1 mol: 0.08-0.17 L, and the mass ratio of the usage of alkali metal fluoride to the usage of hydrochloric acid solution is 1: 5-10.
4. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The MAX phase material in S1 is titanium aluminum carbide, and the mass ratio of the amount of alkali metal fluoride used to the amount of MAX phase material used is 1:0.8-2.
5. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The tin source in S2 includes at least one of tin chloride pentahydrate and stannous chloride, the mass ratio of the tin source to the sulfur source is 1:1-4, and the amount of the tin source added to the water is 0.003-0.01 g / ml.
6. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The amount of the MXene suspension precipitate in S1 is measured in terms of alkali metal fluoride, and the mass ratio of the amount of the alkali metal fluoride to the amount of the tin source in S2 is 1:1.5-4.
5.
7. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: After adding the MAX phase material to the S1, the reaction temperature is 25-35°C, the reaction time is 13-20h, and the ultrasonic time is 0.8-1.5h.
8. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: In the S2, the reaction temperature in the autoclave is 150-180°C, the reaction time is 12-20h, and the ultrasonic time is 0.8-1.5h.
9. The method for preparing a MXene / SnS2 / SnO2 composite material according to claim 1, characterized in that: The ultrasonic time in S3 is 4-8h.
10. A battery comprising a MXene / SnS2 / SnO2 composite material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of composite nano SnO2 negative electrode material and mesophase carbon microspheres
CN112366319A